Administrative and Police Regulation of Muslim Women’s Position in Russian Turkestan - Vyacheslav P. Litvinov (RUDN Journal of Russian History)
The author considers in two contexts the problem of the legal regulation of Muslim women’s position in Russian Turkestan, the Central Asia territories which had become part of Russia - on the one hand, the general state of the women's issue in the Russian Empire, and on the other hand, how the state ensured the rights of the entire local population of the region. Within the text, the role of the imperial police in regulating the legal status of Muslim women is examined. It is emphasized that in various regions of Russia the position of women had its own regional specifics, but it was especially difficult in Islamic Central Asia. However, it is noted that unlike the Bukhara and Khiva khanates, Muslim women of Russian Turkestan gained support from the administration and the po-lice, which helped them resist the traditional provisions of customary law and Sharia. Imperial civil law was considered the norm according to which women could turn to the authorities for protecting their rights. The author also reveals the influence of the new “Regulations on the Administration of the Turkestan Territory” adopted in 1886, which worsened the living conditions of women and left them with the opportunity to protect their rights only through the adoption of Christianity (Orthodoxy). Nevertheless, based on various sources, the article shows that the position of women in the region under Russian rule had significantly improved compared to the pre-imperial period.